Kompetensi pustakawan dalam perspektif Islam - Parhan Hidayat (Al Maktabah, 2014)
Islam is a religion which has comprehensive teachings, including how a Moslem works in libraries. The final goal of works is the same, which is to give the best service to their costumers. To give the best service, librarian should master some competencies. US Special Library Associations has formulated ten individual competencies for librarian. Having analyzed the holy quran, hadits, sahabat and Islamic scholar, it is found that Islam has appropriate teachings to fulfill or to compare with those individual competencies. So that, a good and smart Moslem should be a professional and skillful librarian.